Synchronous Resectable Metastatic Colorectal Cancer. Issue 30 (July 2015) - Fu, Jianfei; Jiang, Mengjie; Tan, Yinuo; Yang, Jiao; Wu, Lunpo; Feng, Lin; Zheng, Shu; Yuan, Ying; Wafi, Attaallah.
<x xml:space="preserve">Abstract</x> Abstract To evaluate the value of lymph node status of primary tumors in predicting the prognosis of synchronous resectable metastatic colorectal cancer (mCRC). The characteristics of resectable mCRC are substantially different from other cancers, and the prognostic factors of resectable mCRC are still controversial. The data of 2007 patients with mCRC who received resection of the primary tumors and metastatic lesions synchronously were reviewed from the Surveillance, Epidemiology and End-Result database. The Kaplan–Meier method was used to evaluate the capacity of different prognostic factors. Univariate and multivariate logistic regression models were used to evaluate the relationship between the lymph node status and other factors. The mRNA profiles of primary resectable mCRC tumors were obtained by microarray at our center. The median survival times were 50, 36, 32, 27, and 19 months in the N0-stage, N1a-stage, N1b-stage, N2a-stage, and N2b-stage subgroups according to the 7th American Joint Committee on Cancer (AJCC) Tumor Lymph Node Metastasis (TNM) N-classification (P = 0.000), and 40, 29, 22, and 15 months in patients with metastatic lymph node ratio (LNR) <0.25, 0.25–0.49, 0.5–0.74, and ≥0.75 subgroups (P = 0.000). In the COX model, the 7th AJCC TNM N-stage and LNR were independent prognostic factors. The mRNA profile was not associated with lymph node involvement. Both the N-stage according to the 7th AJCC TNM staging system and LNR had the capacity to subclassify synchronous resectable mCRC with different prognoses. The lymph node might be integrated into the AJCC staging system as a diagnose-delay prognostic factor for stage IV disease.